OPTIMALISASI TCR MENGGUNAKAN METODE CRASH PROGRAM (Studi Kasus: Proyek Pembangunan Gedung “K” UMP) - isradias mirajhusnita (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2020)
A successful project when the cost of the work is not more than budgeted. The time of work does not exceed the planned time and the specifications are in accordance with the plan or design. The purpose of the authors conducting this research is 1) to find out any work that included in the cross-critical and form of network planning using the QSB windows application, 2) to determine the optimal time and cost of accelerating the time of K building construction projects. This research is using the crash program method. To save time, the acceleration is done by adding overtime hours for 4 hours to the structural work that included the cross-critical, i.e., the 1st-floor structure, 2nd-floor structure, floor structure, 4th-floor structure, 5th-floor structure, 6th-floor structure, 9th-floor structure. After accelerating, the total project time needed after crashing on critical work generated is 175 weekdays with a difference of 58 days from the normal duration of 247 days. The impact caused by the change in time on these costs is the increase in direct costs to Rp. 8,624,930,090.12. Meanwhile, after crashing the duration of the project became shorter, it caused a decrease in indirect costs to Rp. 1,058,595,050.81.